Theoretical studies results for a mathematical model of a road roller turn - M. N. Artemenko; P. A. Korchagin; I. A. Teterina (Вестник СибАДИ)
Introduction. At the heart of the creation and improvement of robotic road construction machines and complexes are mathematical modelling methods, the use of which is justified both in the development of the machines themselves and mathematical models that describe the turning processes and determine the movement of the machine along a given trajectory.The method of research. The article presents a generalized design scheme for the rotation of a three-axle road roller, which reflects its main geometric and kinematic characteristics. On the basis of the design scheme, a mathematical model of the rotation of the skating rink was compiled. As a result of the developed mathematical model, a program code was built in the MATLAB software product, which formed the basis of theoretical studies that made it possible to fully study the influence of the design and operational parameters of the machine on the motion trajectory and positioning accuracy.Results. The calculated dependencies have been obtained to determine the influence of such parameters as the speed of the road roller, the angular speed of the drum rotation on the distance of rebuilding on a parallel course and on the displacement of the rotary drum, that is, on the trajectory and positioning accuracy of the road-building machine.Conclusion. On the basis of the design scheme, a mathematical model of the rotation of the roller was compiled, as a result of which studies were carried out aimed at studying the influence of the design and operational parameters of the machine on the trajectory of the road roller and the accuracy of its positioning on the construction site when performing technological operations.